Upaya Guru dalam Meningkatkan Kemampuan Membaca Peserta Didik Melalui Penerapan Media Gambar dan Huruf di Kelas 1 MI NW Keruak - Nasrullah; Desi Apriana Ningsih; Susi Elmayana; Lisnaini (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2024)
Reading ability is the main basis not only for teaching Indonesian itself but also for teaching other subjects. Currently, there are still many teachers who have not carried out their functions as professional teachers. This research was conducted with objectives 1). to determine students' development in reading ability in class 1 MI NW Keruak and to determine the influence of picture and letter media in reading ability in class I MI NW Keruak. This research is qualitative research carried out. This type of research is descriptive qualitative research, with data collection techniques, using observation, interviews, and documentation methods. Based on the research results: Firstly, to discover the development of students' reading skills in class 1 MI NW Keruak, this has been carried out very well by the class teacher. Several developments are carried out by teachers, including: 1). Teacher as facilitator. 2). Teacher as director. 3). Teacher as a motivator. Second, the influence of picture and letter media on the reading ability of students in class 1 MI NW Keruak is classified as very good and continues to increase every year. Third, there are several benefits of image and letter media in reading, including 1). Supporting factors include a good school environment, good learning media, good learning facilities, and teachers who can make the class lively and full of passion: 2). Inhibiting factors, including students sometimes not going to school, insufficient pocket money, poor student health, there are students from broken homes and the level of intelligence of each student.